IMPLEMENTASI KEBIJAKAN PENGANGKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL DI KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Supiani, Supiani (Katalogis, 2014)
The policy implementation of the village secretaries as the civil servant aimed at creatingwell-order administrationof government and developmentas well as service, and effective people empowerment. The purpose of this study is to analyze and study the implementation of the village secretaries as the civil servants and to investigate the supporting and inhibit factors of that policy which was studies based on the model of policy implementation of George C Edward III on the aspect of communication, resources, disposition and bureaucracry. This type of study was qualitative. The number of informant was 12 persons who were selected by using purposive sampling technique. The result of study reveals that the policy implementationof the appointment of village secretaries as the civil servants had not yet been optimal as indicated by the following results: (1) Communication: there was no socialization from regional government about the policy of regulation of PP 45 2007, (2) the resources of village secretaries did not fulfill with the requirement due to the old age and had no latest academic certificate possession. (3) the dispotion of attitude and behavior of the implementor in the policy implementation of village sectetary appointment to be civil servant did not run well: some village had vacuum of village secretary position.(4) the bureaucracy structure of regional government in the policy implementation had worked well although there was a lack coordination in the appointment of village secretary position. The inhibit factor of the policy implementation was lack of socialization from regional government about the policy and the policy and the regulation of PP 45 2007. The supporting factor was positive responses from the village secretaries for their appointment as the civil servants.